2023
DOI: 10.1039/d3sm00301a
|View full text |Cite
|
Sign up to set email alerts
|

Mode switching of active droplets in macromolecular solutions

Abstract: Typical bodily and environmental fluids encountered by biological swimmers consist of dissolved macromolecules such as proteins or polymers, rendering them even non-Newtonian at times. Active droplets mimic the essential propulsive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Here, spontaneously generated Marangoni stresses at the droplet interface lead to their propulsion . While the propulsion mechanisms mentioned above may differ among the different artificial swimmers, their characteristics remain the same: a directed ballistic motion at short time scales followed by a random motion at longer time scales. , However, the translational and rotational diffusivities depend on various parameters such as swimmer size, the magnitude of the propulsion force , and also the presence of solutes in the surrounding medium. Microswimmer–wall effects have also been known to affect the motion characteristics significantly. Self-propelled JCs have been studied by subjecting them to diversified environments such as externally imposed flow, topological obstacles, , and fluid interfaces ,, or placing them in a pool of passive tracers. Recent studies have also demonstrated tuning of the dynamics of active JCs by altering their surface morphologies. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, spontaneously generated Marangoni stresses at the droplet interface lead to their propulsion . While the propulsion mechanisms mentioned above may differ among the different artificial swimmers, their characteristics remain the same: a directed ballistic motion at short time scales followed by a random motion at longer time scales. , However, the translational and rotational diffusivities depend on various parameters such as swimmer size, the magnitude of the propulsion force , and also the presence of solutes in the surrounding medium. Microswimmer–wall effects have also been known to affect the motion characteristics significantly. Self-propelled JCs have been studied by subjecting them to diversified environments such as externally imposed flow, topological obstacles, , and fluid interfaces ,, or placing them in a pool of passive tracers. Recent studies have also demonstrated tuning of the dynamics of active JCs by altering their surface morphologies. , …”
Section: Introductionmentioning
confidence: 99%
“…For biological swimmers such as Escherichia coli, Patteson et al demonstrated that the elasticity of the polymer solution resulted in an enhanced swimmer speed and reduced tumbling tendency . Very recently, for active droplets in a viscoelastic media, Dwivedi et al demonstrated a Peclet-induced transition in the swimming mode and also deformation in their shapes . For phoretic colloids, numerous theoretical and computational studies have attempted to understand the behavior of self-propelled colloids in complex media. So far, light-activated JCs have been chiefly used to study the dynamics of active JCs in viscoelastic media experimentally. ,,, Gomez-Solano et al demonstrated that the bulk viscoelastic stresses decouple the translational and rotational dynamics of the active JC .…”
Section: Introductionmentioning
confidence: 99%